A novel formulation representation of the equilibrium constant for water gas shift reaction. (30th July 2022) - Wang, Chao-Wen; Peng, Xiao-Long; Liu, Jian-Yi; Jiang, Rui; Li, Xiao-Ping; Liu, Yu-Song; Liu, Shu-Yan; Wei, Lin-Sheng; Zhang, Lie-Hui; Jia, Chun-Sheng
Abstract: In order to meet prominent disagreement for the water gas shift reaction (WGSR) equilibrium constant values obtained from various conventional empirical correlations and mitigate the strong dependence on plenty of experimental data points, here, we report a novel WGSR equilibrium constant formulation representation approach with direct algebraic operation, which only involves experimental data of 3–6 molecular constants for each reactants and products and does not contain the fitting of any experimental equilibrium constant data. The reliability of the developed approach is demonstrated by comparing the predicted values with experimentally measured data and the calculated results with other previous WGSR equilibrium constant correlations. The average absolute deviations between the theoretical values predicted from the developed technique and the directly measured data reported in the literature are 3.993%, 5.970%, 2.418%, 2.083%, 8.659%, 3.733%, and 3.755% for 7 experimental data sets, respectively. Graphical abstract: Image 1 Highlights: We report a novel WGSR equilibrium constant formulation representation approach. This approach only involves 6–3 molecular constants of the reactants and products. Practical applications of this method are verified from comparing the deviations. The developed approach provides direct algebraic operation and high accuracy.